(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
Being harmful to human health, the regular application of chemical-based repellents to manage mosquito populations has disrupted natural ecosystems, led to the growth of pesticide resistance, the resurgence of mosquito populations, and adverse effects on non-target animals. This is why the researchers conducted this study to produce a natural mosquito repellent spray using Tawa-tawa leaves and Lemongrass extract. This study utilized the quantitative-descriptive research design with a purposive sampling technique. The statistical treatment used for this study was a t-test to determine if there is a significant difference between the assessments of the five (5) Chemistry Majors and five (5) Science Education students. The study used a questionnaire as the research instrument to conduct a survey for the two groups of respondents in order to determine the level of acceptability of the Tawa-tawa and Lemongrass Extract as a repellent spray in terms of ingredients, ease of application, affordability, effectiveness, and presentation. The results of this analysis, in terms of ingredients, ease of application, affordability, effectiveness, and presentation, were rated as "Agree." The overall weighted mean for the Chemistry Majors was 3.29, categorized as "Highly Acceptable," while the Science Education group obtained an overall weighted mean of 3.60, also classified as "Highly Acceptable." The t-computed value was 1.3118, with a degree of freedom of 8 and a critical value of 2.306. Therefore, there is no significant difference between the two groups of respondents. In conclusion, the suggestions and recommendations given by the Chemistry Major and Science Education are in addition to other disinfecting agents such as small amounts of hydrogen peroxide. The application is already acceptable, as long as it does not exceed the prices of commercially produced disinfectant. It is acceptable, if the product inhibits the presence of mosquitoes or other targeted organisms then it should do so. The presentation could be improved by the use of a more readable font and logo of the product.